Health and health behaviors in China: Anomalies in the SES-health gradient? - Rui Huang; Hanna Grol-Prokopczyk (Elsevier, 2022)
Objectives: Fundamental Cause Theory (FCT) predicts that higher socioeconomic status (SES) leads to better health outcomes, through mechanisms including health-promoting behaviors. Most studies supporting FCT use data from Western countries. However, limited empirical studies from China, as well as theoretical considerations suggested by China's unique history and culture, raise questions about the generalizability of FCT to the Chinese context. This study explores whether the associations between SES, health behaviors, and health status in Western countries are also observed in China, and to what extent behavioral risk factors explain socioeconomic disparities in Chinese health. Data and method: Using data on adults age 45+ from the nationally-representative 2015 China Health and Retirement Longitudinal Study (CHARLS; n = 14,420), we conduct regressions of multiple health outcomes (self-rated health, disease count, and several common chronic conditions) on demographic characteristics, SES (measured via education and wealth), and behavioral risk factors (smoking, high-frequency drinking, and overweight). To assess whether behavioral risk factors mediate the SES-health association, we use the Karlson, Holm and Breen (KHB) mediation analysis method. Results: Supporting FCT, both education and wealth predict higher self-rated health and lower risk of arthritis. However, inconsistent with FCT, neither education nor wealth predict disease count, diabetes, or hypertension; education shows some positive association with cardiovascular disease; and higher SES is strongly associated with higher risk of dyslipidemia. Prevalence of smoking and high-frequency drinking are flat by wealth and inversely U-shaped by education, while overweight is somewhat concentrated in the highest SES groups. Results of mediation analyses show both suppression and mediation effects. Conclusion: High prevalence of behavioral risk factors across SES groups appears to damage health in much of the Chinese population, and thus attenuates social gradients in health. A broader range of cultural, historical, and political factors should be incorporated into FCT's theoretical framework, particularly in non-Western contexts.